Four ways of being human an introduction to anthropology - Lisitzky, Gene, 1899- (Harmondsworth, Eng. ; New York : Penguin Books, 1956)
Compares the customs and way of life of four primitive races of people--the Semang people of Malay and Siam, the Polar Eskimos, the Maoris of New Zealand, and the Hopi Indians of America--stressing how they have adapted themselves to their different environments.
Reprint of the ed. published by Viking Press, New York.
Includes index.
All age.
Keywords: Semang (Malaysian people).; Polar Eskimos; Maori (New Zealand people).; Hopi Indians; Semang (Malaysian people).; Eskimos; Maori (New Zealand people).; Hopi Indians; Indians of North America